Biomarkers of atrial cardiopathy and embolic stroke of undetermined source: Atrial cardiopathy and ESUS - Semnic, Isidora; Živanović, Željko (Medicinski časopis, 2023)
Research indicates that a pathological atrial substrate can cause embolic stroke even in patients without atrial fibrillation. This condition is called "atrial cardiopathy" and indicates changes in the heart's atria that can precede AF. Subclinical AF can be detected in 30% of patients with an undetermined source stroke (Embolic Stroke of Undetermined Source - ESUS). The objective of this narrative review is to provide, based on the current literature review data on the pathogenesis and markers of atrial cardiopathy and therapeutic possibilities in case of detection of atrial cardiopathy in order to prevent an embolic event. Atrial cardiopathy as a pathological substrate before the development of manifest AF may be a potential mechanism of ESUS. Evaluation of atrial cardiopathy biomarkers PTFV1 (>5,000 µVms), NT-proBNP >250 pg/ml and left atrial enlargement) can be a starting point for ESUS risk identification as well as for timely therapeutic stroke intervention using direct oral anticoagulant therapy (DOAC) in ESUS patients with atrial cardiopathy. To conclude, atrial cardiopathy biomarkers are useful for monitoring patients with atrial cardiopathy who may be at increased risk for developing ESUS. A detailed and complete etiological assessment to classify patients into the ESUS group and dynamic long-term follow-up of patients to detect occult AF are complicating factors for understanding the connection between atrial cardiopathy and ESUS. Further research in the area of atrial cardiomyopathy as a risk factor for ESUS is extremely important for the timely introduction of DOAC.
Keywords: atrial cardiopathy, atrial fibrillation, embolic stroke of undetermined source